Investigating drag reduction characteristic using okra mucilage as new drag reduction agent - Abdulbari, Hayder A.; Siti Nuraffini, Kamarulizam; Rohaida, Che Man (Asian Network for Scientific Information, 2011)
A concern in reserving environment from water pollution is a trigger for this investigation. Abundant source of okra in Malaysia, as well as cheap and easy to get are the advantages. Okra mucilage extracted from okra pod can be additive to reduce drag in pipeline and conserve the energy along pipeline. In this study, the effect of the presence of a Drag Reducing Agent (DRA) on the pressure drop in horizontal pipes carrying water is investigated. An experimental rig is set-up. The test section of the experimental set-up is consisted of: a smooth PVC pipe with length of 50 time pipe diameter connected to rough galvanized iron with 5 testing section 0.5 meter each The employing DRA is a new natural additive which is okra mucilage as polymeric DRA. The percent drag reduction (%DR) is calculated using the obtained experimental data, in presence of the DRA. The results show that addition of DRA could be effective with several doses of DRA after average reading for 5 min. Highest %DR for about 60% is obtained for some experimental conditions. The result shows that okra mucilage is a potential DRA to be use in water transportation.